2020
DOI: 10.47203/ijch.2020.v32i03.009
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoeal diseases and its relation to WaSH practices and MPN count among under-five children residing in Resettlement colony, Delhi

Abstract: Background: Globally, diarrhoeal diseases are the second leading cause of death among under 5 children and India alone accounts for 100,000 lives annually, third highest in the world. In low and middle-income countries, contaminated water has been the major source of diarrhoeal diseases and lack of improper WaSH (Water, Sanitation and Hygiene) practices accounts for 90% of the total death. Aims and Objective: To find out the burden of diarrhoea and its relation to WASH practices among children and mothers/care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…In the case of three out of 10 subjects, the water quality was either suspicious or unsatisfactory. Contrary to this study, higher unsatisfactory water quality was reported in some studies conducted in India [12,17,18].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…In the case of three out of 10 subjects, the water quality was either suspicious or unsatisfactory. Contrary to this study, higher unsatisfactory water quality was reported in some studies conducted in India [12,17,18].…”
Section: Discussioncontrasting
confidence: 96%
“…It was maximum in subjects with the not satisfactory class of water (four out of 15) and minimum with the highly satisfactory class of water (nearly one out of 5). This is similar to a study conducted in Delhi, where six out of 10 children with diarrhoea were consuming unsatisfactory water, 27.7% of the children were drinking water that was of questionable quality, and only one out of 10 children were drinking water that was satisfactory and fit for human drinking purpose [12].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The average processing effects obtained by different matching methods are extremely similar. Therefore, the nearest neighbor matching method is adopted here to deal with samples according to the ratio of 1:1, to obtain the experimental group and the control group [ 27 , 28 ].…”
Section: Research Model On the Impact Of Utcp On Female Employmentmentioning
confidence: 99%